Acessibilidade em ambientes informacionais digitais - Cusin, César Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The current nature of World Wide Web (Web), which highlights the collaborative participation of users in some digital information environments, lead to development of guidelines with a focus on Inclusive Digital Information Architecture for a different audiences in multiples informational ambiences. The concept of digital accessibility aims to include users with special needs in digital information environments, focusing on improving the interaction between subjects and the environment in order to provide improved quality of life. This research proposes guidelines for a inclusive digital information environment, aiming to identify the elements of accessibility that allow the promotion of inclusion digital information, in order to highlight the references of the Architecture of Digital Information, the international recommendations and the structures representation of information (specially accessibility attributes), with the look of Information Science and New Technologies of Information and Communication. The research have the follow hypotheses: the accessibilities attributes used to represent the content in digital information environments do not satisfactorily contemplate descriptions of digital resources that supplies the special needs of users; the Information Architecture needs new elements of digital accessibility with a focus on special needs of users, international accessibility guidelines, in a singular way, does not provide subsidies to a universal access. The thesis is as to the need to develop methodologies with guidelines that contemplate the elements of digital accessibility focused on the task of the user. The research problem is that actual methodologies and recommendations used for the development of digital information environments do not cover all the elements of accessibility with a focus on user needs. The proposition is to present, through a methodological approach... (Complete abstract click electronic access below)

A natureza atual da World Wide Web (Web) que destaca a participação colaborativa dos usuários em diversos ambientes informacionais digitais conduz ao desenvolvimento de diretrizes que enfocam a Arquitetura da Informação Digital Inclusiva para diferentes públicos nas mais diversas ambiências informacionais. O conceito de acessibilidade digital visa à inclusão de usuários com deficiência em ambientes informacionais digitais, com foco na melhoria da interação dos sujeitos com o ambiente de modo a proporcionar a melhoria de qualidade de vida. A pesquisa propõe diretrizes para um ambiente informacional digital inclusivo, visando apontar os elementos de acessibilidade que permitem a promoção da inclusão informacional digital, de forma a destacar os referenciais da Arquitetura da Informação Digital, de recomendações internacionais e das estruturas de representação das informações, em especial dos atributos de acessibilidade, com o olhar da Ciência da Informação e das novas Tecnologias de Informação e Comunicação. Têm-se como hipóteses: os atributos de acessibilidade utilizados para representação de conteúdos em ambientes informacionais digitais não contemplam satisfatoriamente as descrições dos recursos digitais que atendam as necessidades especiais dos usuários; a Arquitetura da Informação carece de novos elementos de acessibilidade digital com foco nas necessidades especiais dos usuários; as recomendações de acessibilidade internacionais, isoladamente, não fornecem subsídios para o acesso universal. Tem-se como tese a necessidade de desenvolvimento de metodologias com diretrizes que contemplem os elementos de acessibilidade digital focados na tarefa do usuário. Como problema de pesquisa tem-se que a de que as atuais metodologias e recomendações utilizadas para o desenvolvimento de ambientes informacionais digitais não contemplam integralmente...
Keywords: Tecnologia da informação; Inclusão digital; Web colaborativa; Inclusão informacional digital; Ambientes informacionais digitais; Arquitetura da informação digital inclusiva; Acessibilidade Web (W3C/WAI) - Guias de; Accessibility; Digital Informational Environment; Digital Inclusion; Web Accessibility Guidelines (W3C/WAI)